The microeconomic determinants of emigration and return migration of the best and brightest: evidence from the Pacific - John Gibson; David McKenzie (Institute for the Study of Labor (IZA), 2009)
A unique survey which tracks worldwide the best and brightest academic performers from three Pacific countries is used to assess the extent of emigration and return migration among the very highly skilled, and to analyze, at the microeconomic level, the determinants of these migration choices. Although we estimate that the income gains from migration are very large, not everyone migrates and many return. Within this group of highly skilled individuals the emigration decision is found to be most strongly associated with preference variables such as risk aversion, patience, and choice of subjects in secondary school, and not strongly linked to either liquidity constraints or to the gain in income to be had from migrating. Likewise, the decision to return is strongly linked to family and lifestyle reasons, rather than to the income opportunities in different countries. Overall the data show a relatively limited role for income maximization in distinguishing migration propensities among the very highly skilled, and a need to pay more attention to other components of the utility maximization decision.
urn:nbn:de:101:1-20090119226
Keywords: O15; F22; J61; 330; Brain drain; brain gain; highly skilled migration; return migration; selectivity; Brain Drain; Hochqualifizierte Arbeitskräfte; Auswanderung; Rückwanderung; Migrationstheorie; Pazifischer Raum; USA